RELEX: An Excel-based software tool for sampling split-half reliability coefficients. (November 2020) - Steinke, Alexander; Kopp, Bruno
Abstract: Split-half reliability provides a method for estimating inter-item reliability of measures obtained from repeatedly administered items (or trials). We introduce RELEX ; a freely available, Microsoft Excel-based software tool that randomly assembles test halves, yielding a sampling-based distribution of split-half reliability coefficients. Estimates of parallel, tau-equivalent, and congeneric split half reliability are reported. RELEX offers a graphical user interface, and provides freely eligible numbers of sampled splits as well as easy handling of missing values and variable trial or item numbers. Results are summarized in the form of a histogram, along with measures of its central tendency and uncertainty.